Enhancing productivity of summer sesame (Sesamum indicum) on paddy fallows through optimization of fertilizer, planting geometry and genotypes - KUMARA, B H PRASANNA; CHITTAPUR, B M; HIREMATH, S M; MALLIGWAD, L H (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during summer 2007 and 2008 at ARS, Mugad, Karnataka on paddy fallows to study the response of sesame (Sesamum indicum L.) genotypes to levels of fertilizer and planting geometry. Of the three cultivars, DS 1 and E 8 were comparable (1 200 and 1 164 kg/ha seeds, respectively) and were superior to DSS 9 (944 kg/ha) both in terms of seed yield and income, while increasing dose of fertilizer had no significant influence on any of the parameters studied. Higher population with 30/40 cm × 10 cm recorded higher seed yield and net income compared to 30/40 cm × 20 cm planting geometries. Among all, cultivar DS 1 recorded significantly higher seed yield (1 393 kg/ha) with recommended NPK (40:25:25 kg/ha, respectively) and spacing (30 cm × 10 cm). At 150 % recommended NPK and 45 cm × 10 cm spacing DS 1recorded higher N uptake (86.16 kg/ha) than cv. E 8 receiving recommended NPK and spacing (77.26 kg/ha). P uptake was also higher in same genotype and fertilizer level with 30 cm × 20 cm spacing (4.38 kg/ha) over cv. DSS 9 receiving recommended NPK and spacing. DS 1 with closer spacing of 30 cm × 10 cm and 100% NPK recorded significantly higher net returns and B:C ratio (` 43 268 and 4.48, respectively).